Two Close Friends Fulfil Their Dreams to Enroll at UMPSA - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PAYA BESAR, August 13, 2023 - Two close friends from Kampung Cherong and Pos Sinderut shared their joy and excitement as they received offers to pursue their studies in the Diploma in Occupational Safety and Health programme at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), which began registering today.